ANALISIS PENDAPATAN USAHATANI BAWANG MERAH DI DESA GUNTARANO KECAMATAN TANANTOVEA KABUPATEN DONGGALA - Suratno Suratno; Christoporus Christoporus; Dance Dance (Universitas Tadulako, 2022)
The local hammer onion plant is one of the sources of i ncome for the people of the central Sulawesi who work in the agricultural sector and is also a source of local revenue, the local hammer onion plane plant has become and important commodity in central Sulawesi because it is an exsport commoditi for the central Sulawesi region. In general, an increase in the production of a farm cant be an indicator of the success of the farm in question, however the high production of a commoditi obtained by land area unity does not guarantee the high in come of shallot farming which is influencet by the price received by the farmer and the cost of using farm inputs. This study aims to the termine how mucth in come of shallot farming. Respondents were the terminate using simple random sampling method. The numbers of respondents who were a ssigned as samples in this study where 31 people from a total population off 108 people. The results showed that the average in come of shallot farming in the village of Guntarano was Rp. 19.076.532,26/ 0,74 ha/MT or Rp. 25.779.097,66/ha/MT.